Gravity in the quantum lab - Howl, Richard; Hackermüller, Lucia; Bruschi, David Edward; Fuentes, Ivette (Taylor & Francis, 2017)
At the beginning of the previous century, Newtonian mechanics was advanced by two new revolutionary theories, Quantum Mechanics (QM) and General Relativity (GR). Both theories have transformed our view of physical phenomena, with QM accurately predicting the results of experiments taking place at small length scales, and GR correctly describing observations at larger length scales. However, despite the impressive predictive power of each theory in their respective regimes, their unification still remains unresolved. Theories and proposals for their unification exist but we are lacking experimental guidance towards the true unifying theory. Probing GR at small length scales where quantum effects become relevant is particularly problematic but recently there has been a growing interest in probing the opposite regime, QM at large scales where relativistic effects are important. This is principally because experimental techniques in quantum physics have developed rapidly in recent years with the promise of quantum technologies. Here we review recent advances in experimental and theoretical work on quantum experiments that will be able to probe relativistic effects of gravity on quantum properties. In particular, we emphasise the importance of using the framework of Quantum Field Theory in Curved Spacetime (QFTCS) in describing these experiments. For example, recent theoretical work using QFTCS has illustrated that these quantum experiments could also be used to enhance measurements of gravitational effects, such as Gravitational Waves (GWs). Verification of such enhancements, as well as other QFTCS predictions in quantum experiments, would provide the first direct validation of this limiting case of quantum gravity.